1994
DOI: 10.1155/dte.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Management of Pancreatic Pseudocysts

Abstract: Recently, endoscopic interventional procedures were introduced for nonsurgical therapy of symptomatic pancreas pseudocysts. We reported 25 patients treated by endoscopic retrograde pancreas drainage (ERPD), endoscopic cystogastrostomy (ECG), or endosopic cystoduodenostomy (ECD). ERPD was performed in 9 patients by placement of a 5 Fr. or 7 Fr. endoprosthesis transpapillary into the cyst or the main pancreatic duct. ECG was carried out in 10 cases, in 7 of these, a double pigtail catheter was additionally inser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…This scenario is reported to occur in 40-69% of pseudocysts [65][66][67] and is more common in patients with chronic pancreatitis (49%) than those with acute pancreatitis (20%) [68]. In a review of six studies with a total of 117 patients [68][69][70][71][72][73], initial success rates were 84%, with a long-term success rate of 75% after 2 years. Recurrence was 9% over 2 years.…”
Section: Endoscopic Management Of Pancreatic Pseudocystsmentioning
confidence: 99%
See 1 more Smart Citation
“…This scenario is reported to occur in 40-69% of pseudocysts [65][66][67] and is more common in patients with chronic pancreatitis (49%) than those with acute pancreatitis (20%) [68]. In a review of six studies with a total of 117 patients [68][69][70][71][72][73], initial success rates were 84%, with a long-term success rate of 75% after 2 years. Recurrence was 9% over 2 years.…”
Section: Endoscopic Management Of Pancreatic Pseudocystsmentioning
confidence: 99%
“…A 7-to 10-F stent is often left traversing the cystgastrostomy; it is left in place for 2-4 months, or until imaging verifies pseudocyst resolution. In a combined series of 61 patients [69,72,[76][77][78][79][80], the initial success rate was 77% and long-term success rate was 59%. Recurrence was 18% with a follow-up from 9 to 48 months.…”
Section: Endoscopic Management Of Pancreatic Pseudocystsmentioning
confidence: 99%
“…Its predictive factors of success include the presence of strictured areas, the pseudocysts size over 6 cm in diameter, location in the body of the pancreas and an evolution of the pseudocyst of less than 6 months (29). As far as the procedure's safety is concerned, there is a low morbidity and no reported mortality in patients submitted to this maneuver (29,(31)(32)(33)(34)(35). Among possible complications, hemorrhage is reported in less than 1% of cases, postprocedural pancreatitis in 5% of cases while stent migration is considered extremely rare (29,(31)(32)(33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%
“…As far as the procedure's safety is concerned, there is a low morbidity and no reported mortality in patients submitted to this maneuver (29,(31)(32)(33)(34)(35). Among possible complications, hemorrhage is reported in less than 1% of cases, postprocedural pancreatitis in 5% of cases while stent migration is considered extremely rare (29,(31)(32)(33)(34)(35). Some authors reported stent obstruction in secondary infections of the pseudocyst, in which case stent change alone may be the only necessary maneuver (29,34,35).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation